Tahfidz Activity Development Using the Talaqqi Method at High School Level in the Ramadhan Pesantren Program at Surau Istighfar Banda Puding - Ahmad Faiz; Martin Kustati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This coaching aims to help students memorize verses of the Al-Qur'an in the Ramadhan Islamic boarding school program where one of the activities is tahfidz activities, especially juz 30. This coaching is motivated by the fact that there are still many deficiencies in students, especially high school level, in reciting verses of the Al-Qur'an. which is not in accordance with the correct rules of recitation, making it difficult for students to memorize verses in the Ramadhan Islamic boarding school program. The method used in this assistance is the Talaqqi Method. The Talaqqi method is the correct method among the many methods of memorizing the Al-Qur’an. This method is implemented by the educator starting to read a piece of verse then continuing with the students repeating the reading read by the educator first. This implementation method is the PAR (Participary Action Research) methodology, an approach whose process aims at learning in overcoming problems and meeting the practical needs of society, as well as the production of knowledge. The result of mentoring using the Talaqqi Method is that students in reciting Al-Qur'an verses have fulfilled the correct recitation of tajwid rules. In terms of memorization, students easily memorize verses of the Al-Qur’an.